Stress and Social Adaptation in Cat Owners: The Effect of Pet Attachment - Nur Rahmadani; Adnan Achiruddin Saleh (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2025)
This study aimed to determine the effect of pet attachment on stress levels and social adaptation in cat owners. The researcher used a quantitative approach with a multivariate linear regression design. A total of 32 students were selected as participants using a total sampling technique. The instrument used was a Likert model questionnaire of 150 items with Cronbach's Alpha reliability and Pearson Product Moment validity test. Data were analyzed using simple linear regression and multivariate testing (MANOVA) through the SPSS version 25 program. The findings showed that pet attachment significantly affected social adaptation and stress levels in cat owners (F = 97.634 and Sig. = 0.000). The contribution of pet attachment to social adaptation was 19.9% ”‹”‹, and to stress was 86.5%. The implications of this study lead to the development of psychological support strategies based on interactions with pets to improve students' emotional and social well-being.